Activation of Sirt1/FXR Signaling Pathway Attenuates Triptolide-Induced Hepatotoxicity in Rats - Yang, Jing; Sun, Lixin; Wang, Lu; Hassan, Hozeifa M.; Wang, Xuan; Hylemon, Phillip B.; Wang, Tao; Zhou, Huiping; Zhang, Luyong; Jiang, Zhenzhou (Frontiers in Pharmacology, 2017)
Triptolide (TP), a diterpenoid isolated from Tripterygium wilfordii Hook F, has an excellent pharmacological profile of immunosuppression and anti-tumor activities, but its clinical applications are severely restricted due to its severe and cumulative toxicities. The farnesoid X receptor (FXR) is the master bile acid nuclear receptor and plays an important role in maintaining hepatic metabolism homeostasis. Hepatic Sirtuin (Sirt1) is a key regulator of the FXR signaling pathway and hepatic metabolism homeostasis. The aims of this study were to determine whether Sirt1/FXR signaling pathway plays a critical role in TP-induced hepatotoxicity. Our study revealed that the intragastric administration of TP (400 μg/kg body weight) for 28 consecutive days increased bile acid accumulation, suppressed hepatic gluconeogenesis in rats. The expression of bile acid transporter BSEP was significantly reduced and cholesterol 7α-hydroxylase (CYP7A1) was markedly increased in the TP-treated group, whereas the genes responsible for hepatic gluconeogenesis were suppressed in the TP-treated group. TP also modulated the FXR and Sirt1 by decreasing its expression both in vitro and in vivo. The Sirt1 agonist SRT1720 and the FXR agonist obeticholic acid (OCA) were used both in vivo and in vitro. The remarkable liver damage induced by TP was attenuated by treatment with either SRT1720 or OCA, as reflected by decreased levels of serum total bile acids and alkaline phosphatase and increased glucose levels. Meanwhile, SRT1720 significantly alleviated TP-induced FXR suppression and FXR-targets involved in hepatic lipid and glucose metabolism. Based on these results, we conclude that Sirt1/FXR inactivation plays a critical role in TP-induced hepatotoxicity. Moreover, Sirt1/FXR axis represents a novel therapeutic target that could potentially ameliorate TP-induced hepatotoxicity.